Genetic differences in protein requirement of growing swine - Maner, JH; Rounsaville, TR; Gallo, JT; Pound, WG; VanVleck, LD (1977)
Crossbred Duroc × Hampshire-Landrace (D × HL) pigs from 24 litters were assigned at 56 days of age to either a standard corn-soybean meal-type diet containing 16% protein or a similar diet containing 10% protein. Of 66 pigs fed 16% protein (53 females, 13 males), 13 females and three males were chosen at random after 42 days on test to constitute the control breeding population for the next generation. Of the 66 pigs fed 10% protein, the 13 females and three males with the highest body weight gain during 42-day test and the 13 females and three males with the lowest body weight gain were selected to constitute the selected breeding populations for the next generation. Each of the three breeding populations was mated at random within itself two times to obtain information on two parities for each parent population. All breeding groups were fed and housed similarly throughout the remainder of the life cycle. Progeny from the above matings were tested during a 42-day period beginning at 56 days of age. There were significant effects of treatment and of parity and there was a significant treatment x parity interaction. Multiple comparison of means indicated that control group progeny fed 16% protein did not gain faster (P>.05) than pigs fed 10% protein whose parents were selected for rapid weight gain on the low protein diet. Estimates of realized heritability were .11, .71 and .35 for first and second parity, and the weighted average of both parities, respectively. These estimates indicate that sufficient genetic variability exists for weight gain of pigs fed low protein diets to make selection worthwhile.